Improving the impact resistance of concrete panels by glass fiber reinforced polymer sheets. Issue 2 (June 2017) - Abdel-Kader, Mohamed MA; Fouda, Ahmed
In this article, the response of 12 plain concrete specimens to an impact of hard projectiles was examined in an experimental study. The tests were planned with an aim to observe the influence of using glass fiber reinforced polymer sheets to strengthen plain concrete panels on the performance of concrete under this type of loading. The main findings show that strengthening plain concrete panels with glass fiber reinforced polymer sheets showed satisfactory performance under the impact load; the glass fiber reinforced polymer sheets can be used for strengthening or upgrading concrete structures to improve their resistance against impact. Also, the location of the glass fiber reinforced polymer sheet affects the front and rear face craters.